2013
DOI: 10.1093/jxb/ert319
|View full text |Cite
|
Sign up to set email alerts
|

Leaf mesophyll conductance and leaf hydraulic conductance: an introduction to their measurement and coordination

Abstract: Two highly contrasting variables summarizing the efficiency of transport of materials within the leaf are recognized as playing central roles in determining gas exchange and plant performance. This paper summarizes current approaches for the measurement of mesophyll conductance to CO2 (g m) and leaf hydraulic conductance (K leaf) and addresses the physiological integration of these parameters. First, the most common methods to determine g m and K leaf are summarized. Next, novel data compilation is analysed, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
207
5
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 200 publications
(218 citation statements)
references
References 123 publications
5
207
5
1
Order By: Relevance
“…We note that there are a number of other methods in use for determining K leaf , such as the high-pressure flow method (Yang and Tyree, 1994), the rehydration kinetics method (Brodribb and Holbrook, 2003), and the vacuum pump method (Martre et al, 2001; for review of methods and their contrasting assumptions and difference in simulated flow pathways, see Sack and Tyree, 2005;Flexas et al, 2013). Although several studies have shown that the different methods tend to yield similar maximum K leaf values (Sack et al, 2002;Scoffoni et al, 2008), we highly recommend the use of the evaporative flux method for the most accurate representation of outside-xylem hydraulic pathways, since water movement in this method would most closely resemble that of a naturally transpiring leaf.…”
Section: Computing Integrated Leaf-level Hydraulic Conductancesmentioning
confidence: 99%
“…We note that there are a number of other methods in use for determining K leaf , such as the high-pressure flow method (Yang and Tyree, 1994), the rehydration kinetics method (Brodribb and Holbrook, 2003), and the vacuum pump method (Martre et al, 2001; for review of methods and their contrasting assumptions and difference in simulated flow pathways, see Sack and Tyree, 2005;Flexas et al, 2013). Although several studies have shown that the different methods tend to yield similar maximum K leaf values (Sack et al, 2002;Scoffoni et al, 2008), we highly recommend the use of the evaporative flux method for the most accurate representation of outside-xylem hydraulic pathways, since water movement in this method would most closely resemble that of a naturally transpiring leaf.…”
Section: Computing Integrated Leaf-level Hydraulic Conductancesmentioning
confidence: 99%
“…Contrary to water transport systems, leaf vein systems show great variation in arrangement, density, vascular bundle features and xylem conduits within the bundles (Sack and Scoffoni, 2012). In grapevine, leaf water movement suggested to be influenced by mesophyll architecture which contributes to water flux in the mesophyll and water evaporation at the cell wall surface (TomĂĄs, 2012;Flexas et al, 2013). On the other hand, Martorell et al (2015) found in two V. vinifera cultivars (Tempranillo and Grenache) that leaf vulnerability at 50 % and 80% loss of K leaf (P50 and P80) as well as the maximum K leaf decreased seasonally by more than 20%.…”
Section: Morpho-hydraulics and Water Transportmentioning
confidence: 99%
“…A positive relationship between g m and g s has been reported in several studies (Barbour et al, 2010;Gu et al, 2012;Flexas et al, 2013aFlexas et al, , 2013b, although two studies in wheat (Triticum aestivum) detected no relationship between g m and g s (Jahan et al, 2014;Barbour et al, 2016). It is not yet clear if the coordination between g m and g s is associated with the independent scaling of both diffusional conductances with the overall physiological activity of leaves or if there is an underlying mechanistic relationship we have yet to appreciate (e.g.…”
mentioning
confidence: 95%
“…It is not yet clear if the coordination between g m and g s is associated with the independent scaling of both diffusional conductances with the overall physiological activity of leaves or if there is an underlying mechanistic relationship we have yet to appreciate (e.g. reliance on the same aquaporins in both the diffusion path of CO 2 and the outside-xylem portion of hydraulic flow; Flexas et al, 2013b). Given the potential for coordination between g m and g s , the absolute value of g m may be less of a determinant to improving WUE than is the relative value of g m to g s (i.e.…”
mentioning
confidence: 99%